Nigrospora oryzae causing human corneal keratitis: A case report - Takuya Takayama; Satoru Inoda; Akira Watanabe; Hidetoshi Kawashima (American Journal of Ophthalmology Case Reports, 2024)
[Abstract]: Purpose: We report a rare case of microbial keratitis caused by Nigrospora oryzae. Observations: A 72-year-old Japanese woman was injured by plant debris and developed oval corneal ulcers and hypopyon in the anterior chamber. After 5 days, she complained of pain, redness, and vision loss in her left eye and was treated with antibacterial eye drops and an ointment (1.5 % levofloxacin hydrate, cefmenoxime hydrochloride, and sterilization and disinfection eye drops; SAN-IODE and ofloxacin ophthalmic ointment). Examination revealed a worsening oval corneal ulcer with Descemet's folds and a faint hypopyon. Considering the infection from soil or plants and the poor response to intensive antibacterial eye drops, topical antifungal eye drops, i.e., 1 % voriconazole eye drops, and 1 % natamycin ointment were applied. Direct microscopy of the corneal scraping with Gram staining was performed and the result was negative. Cultures from corneal scrapings showed the growth of dark colonies after several days. The colony was identified as Nigrospora oryzae by sequencing of the fungal internal transcribed spacer region. Pain and vision loss improved with improvement in corneal ulcers. The antifungal treatment was administered for 37 days. Discontinuation of the eye drops after 1 month did not result in keratitis recurrence. At the final follow-up at 70 days, the best-corrected visual acuity was 20/25, with persistent small corneal opacity. Conclusions and importance: Here, we report a case of fungal keratitis caused by Nigrospora oryzae. Microbiological identification of the causes of rare infections is difficult in clinical laboratories, necessitating the use of advanced molecular techniques based on amplification and sequencing of appropriate phylogenetic markers. Nigrospora oryzae responds to topical voriconazole and natamycin.